TRAINING ON DESIGNING INTERACTIVE LEARNING MEDIA-BASED AI (ARTIFICIAL INTELLIGENCE) AT SMPN 1 PLUMBON - Rahmatudin, Jajang; Musyarofah, Siti; Arrofilah, Syifa Fijri; Widyawati, Tiwi; Ahyani, Hisyam; Atifah, Shoimatul (Ann Publisher, 2024)
Abstract: SMPN 1 Plumbon is one of the public schools in Cirebon Regency. Based on the results of observations, SMPN 1 Plumbon already has facilities that support digital-based learning. Technology can help teachers be more creative in developing learning in the classroom. One way to expand learning in the school is by utilizing creative learning media so students can be more active. Learning media can facilitate the achievement of specific learning goals. Based on this description, Community Service (PKM) was carried out on learning media in the form of a learning media workshop with the theme